1995
DOI: 10.1007/bf00183596
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced retinopathy in the newborn rat: effects of hyperbarism and topical administration of timolol maleate

Abstract: The highly significant protective effects of hyperbarism and timolol observed in this study are not fully understood. We speculate that vasoconstriction induced by the hyperbarism reduces the amount of oxygen that reaches the retina from the choroid during O2 supplementation, while an increased ocular perfusion pressure caused by timolol-induced reduction of the intraocular pressure might decrease the stimulus to vasoproliferation that normally occurs with room-air recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…FITC dextran has been used to map the angiogenesis in OIR model in the retinal flat mounts. While adopting the similar procedure, the present study has also observed an avascularised junction between the mid zone of retina and the ora serrata along with microaneurysm which are similar to the findings of others [18, 19, 20]. In order to compare the effect of RRAS blockade with control, this study opted for ERG and retinal vascular tortousity as quantifiable parameters.…”
Section: Discussionsupporting
confidence: 86%
“…FITC dextran has been used to map the angiogenesis in OIR model in the retinal flat mounts. While adopting the similar procedure, the present study has also observed an avascularised junction between the mid zone of retina and the ora serrata along with microaneurysm which are similar to the findings of others [18, 19, 20]. In order to compare the effect of RRAS blockade with control, this study opted for ERG and retinal vascular tortousity as quantifiable parameters.…”
Section: Discussionsupporting
confidence: 86%
“…51 In vivo, oxygen induced rethinopathy in newborn rats was inhibited by timolol treatment. 52 Timolol also displays protective effects against the neuronal damage induced by glutamate in rat retina, 40 further confirming the antioxidant attitude of timolol because glutamate exerts its cytotoxicity through oxidative damage, as demonstrated in retinal ganglion cells. 53 The MTT test used under our experimental conditions specifically evaluates mitochondrial function.…”
Section: Discussionmentioning
confidence: 68%
“…Their peripheral retina was avascular, suggesting that the retinal vascular growth had been retarded. As size of avascular area is correlated with disease severity, this avascular zone is likely to be significant (24,25). The central capillary density in this group was higher than controls and showed smaller capillary-free zones around the larger vessels.…”
Section: Discussionmentioning
confidence: 76%